Boas práticas de manipulação, condições higiênico-sanitárias e composição mineral de sururu (Mytella falcata) comercializado em feiras livres de Alagoas - Lucena, Vívian da Silva Santos (2022)
Sururu (Mytella falcata) is the main fishing resource of the Mundaú-Manguaba Estuarine- Lagoon Complex (MMELC), being a fundamental product for generating income for tens of thousands of families that live in the surroundings of the lagoons. In addition to its natural propensity to accumulate contaminants present in the aquatic environment, such as toxic metals, the handling of sururu is inadequate, from the subsequent stages of its collection to its disposal in the commercialization places. The present study aimed to carry out a diagnosis of good handling practices, hygienic-sanitary conditions and mineral composition of sururu in street markets in the municipalities bathed by the lagoons that make up the MMELC. For that, a checklist was prepared and applied to guide the observation of the hygienic conditions of the facilities, equipment and utensils used, handling and way of exposing the product, clothing and use of personal protective equipment, and waste disposal, among others, at the fairs in Maceió (Tabuleiro), Marechal Deodoro, Pilar, Satuba and Rio Largo. For the investigation of minerals, samples were acquired from all points of sale found in the fairs of the aforementioned municipalities. After procedures to obtain the extracts by acid digestion, the concentrations of iron (Fe), copper (Cu), manganese (Mn) and zinc (Zn) were analyzed, using the atomic absorption spectrophotometry technique, and lead (Pb), following the corresponding protocol of the Standard Methods for the Examination of Water and Wastewater (SMEWW). With the application of the checklist, it was possible to classify the hygienic-sanitary conditions in all the fairs visited as unsatisfactory. Despite this, it is worth noting that the highest percentages of adjustments were observed at the Rio Largo fair, where the assignment of space for commercialization was conditioned to participation in a training course in good food handling practices, offered by the municipality. The research also involved the application of a questionnaire for the socioeconomic characterization of the vendors. It could be noticed the predominance of female vendors, with low schooling, the sale of sururu and/or other fish as the only source of income, reaching a value close to the minimum wage. As for the micromineral composition, iron showed the highest concentrations in all samples, surpassing by more than fifteen times the values detected for copper, manganese and zinc. Regarding the toxic metal lead, the samples were within the limit allowed in bivalve molluscs. The results obtained with this work confirm the importance of sururu for countless families who sell it in open markets to earn a living and reinforce the need for a joint effort, by the market vendors and those responsible for managing these spaces, to provide the population of these locations with an environment conducive to commercialization of food. In addition, it is necessary for the competent authorities to continuously investigate the levels of highly toxic trace elements in the MMELC, so that the benefits of the consumption of sururu by the population are not counterbalanced by the risk of contamination.